Entropy Analysis of a Valveless Piezoelectric Pump With Hyperbolic Tubes - Yang, Qing; Chen, Jun (Frontiers in Energy Research, 2022)
In order to solve the problems of large reflux and low output performance of the valveless piezoelectric pump with conical tubes, the valveless piezoelectric pump with hyperbolic tubes was proposed. However, the previous research only paid attention to the difference of forward and reverse flow resistance inside the tubes. For this reason, the prototypes of conical tube valveless piezoelectric pump and hyperbolic tubes valveless piezoelectric pump were fabricated in this paper. The maximum output flow rate of the valveless piezoelectric pump with hyperbolic tubes was 54 ml/min. Subsequently, the size and position of entropy production of the hyperbolic tube and the conical tube were numerically calculated based on entropy production theory in this paper. The results show that the entropy production rate of the hyperbolic tube was significantly lower than that of the conical tube, which is consistent with the experimental results. This research analyzed the energy loss inside the valveless piezoelectric pump by using the entropy generation theory, and provided a new design and research method for improving the output performance of the valveless piezoelectric pump in the future.